PROCAMALLANUS (SPIROCAMALLANUS) INOPINATUS (NEMATODA: CAMALLANIDAE) PARASITANDO ASTYANAX ALTIPARANAE GARUTTI & BRITSKI, 2000 (CHARACIFORMES; CHARACIDAE) COLETADO NO RIO DO PEIXE, ESTADO DE SÃO PAULO, BRASIL. - Alves, Karina Gabriele Dias; Craveiro, Talita; Azevedo, Rodney Kozlowiski de; Silva, Reinaldo José da; Kozlowiski, Vanessa Doro Abdallah (Electronic Journal "Fórum Ambiental da Alta Paulista", 2011)
.